The Learning outcome of using Augmented Reality Instruction to Enhance Students’ English Vocabulary Learning in the EFL Elementary School - Chin-Huang Daniel Liao; Huang Hsun-Hui; Chang Tin-Chang (FKIP Unismuh Makassar, 2023)
As for the rapid advance in technology, language instructors must search for a new methodology to educate students in technological instruction. This study aimed to explore the learning achievement with AR technology. This study examined the learning outcomes of English vocabulary learning in an AR instruction classroom with technological devices. 51 fourth -grader students participated in the instruction in Taichung city in Taiwan. The experimental method was employed to analyze learning data, including AR instruction(ARI) pre- and post-test, multimedia ppt instruction(MPI) pre- and post- test, and significant t -test. The total of 25 students from the experimental group experienced the ARI method, while 26 other students from the controlled group experienced the MPI method. The result revealed that AR instruction was a significant difference level(p<.001). Comparing ARI and MPI group, the mean score post-test of the AR instruction group(M=92.59) was better than the multimedia ppt group(M=84.86). As for learning improvement, the improvement percentage of AR instruction(I=23.1) was higher than multimedia ppt instruction(I=14.24). Therefore, the results from the data analysis revealed that AR instruction facilitated EFL students’ learning and significantly improved the students’ English vocabulary achievement.